STRATEGI PENINGKATAN UMKM INDUSTRI KERAMIK DI KABUPATEN BANJARNEGARA - Nurmalitasari, Wahyu Intan; Nurcahyanto, Herbasuki (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
SMEs of ceramic industry is one of the charms of Banjarnegara. SMEs of ceramic industry in Banjarnegara has a major contribution to Regional Revenue and is able to create a business field that employs many workers, so assessed as having an important role in the economy of communities of Banjarnegara district. The purpose of this study is to formulate the strategies for improving SMEs of ceramic industry in Banjarnegara. This study uses a descriptive qualitative research design with an informant from Department of Industry, Trade, Cooperatives and SMEs Banjarnegara and the craftsmen from SMEs of ceramic industry in Banjarnegara. The analysis process begins with identifying the internal and external environment in Department of Industry, Trade, Cooperatives and SMEs Banjarnegara using the SWOT analysis to obtain the strategic issues which are then tested with the litmus test. The results of the strategies for improving SMEs of ceramic industry in Banjarnegara study through the SWOT analysis are six issues of strategy. Based on the results of litmus test, the strategies for improving SMEs of ceramic industry in Banjarnegara with the highest score that is Improving services through the development of SMEs of ceramics industry by the high interest of the craftsmen and Improve the stakeholder involvement by utilizing the banking institutions.